SIGNALS STATISTICAL CHARACTERISTICS OF THE MULTICHANNEL SYSTEMS WITH OFDM - Bondarev, B. M.; Kabak, V. S. (Radio Electronics, Computer Science, Control, 2014)
The accurate definition of the found in literature baseband signals statistical characteristics (distribution, numerical results, peak-toaverage ratio) in the multichannel systems with orthogonal frequency-division multiplexing (OFDM) is studied. Not strictly correct variable normalization and discrepancies in peak-to-average ratio estimation with using of Rayleigh distribution for envelope are noted. New results for peak-to-average ratio meanings are obtained. The acceptability of exceeding by threshold value signal on one or several clock intervals is shown, this appears as pulse disturbance on these intervals at all channels. The obtained results allow to reduce the demands on 2–4 dB to dynamic range and linearity of amplitude characteristic of multichannel systems apparature with OFDM